Cholecystectomy during COVID-19: A Single-Center Experience - Nnaji, Martin; Murcott, David; Salgaonkar, Hrishikesh; Aladeojebi, Adebimpe; Athwal, Tejinderjit; Cheruvu, Chandra V. N. (Digestive Disease Interventions, 2021)
COVID-19 pandemic has impacted health care globally with restructuring and prioritization of health care services. We prospectively analyzed 104 patients who underwent laparoscopic cholecystectomy during the peak of COVID-19 in 2020 and compared with 217 patients from the same period in 2019. Emergency admissions constituted majority of cases with no statistical difference between both groups (p = 0.49). Most cholecystectomies were for biliary colic (41.3 vs. 35.5%) and cholecystitis (37.5 vs. 43.8%) without any statistically difference (p = 0.31 and p = 0.29, respectively). This study demonstrates that laparoscopic cholecystectomy was feasible and safe in patients with symptomatic gall bladder disease during the peak period for COVID-19.
Keywords: COVID-19; gall stone disease; cholecystectomy